2021
DOI: 10.1016/j.mgene.2020.100831
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of miRNAs targeting SARS-CoV-2 host cell receptor ACE2

Abstract: In late December 2019, several cases of pneumonia of unknown etiology (COVID-19) were reported in Wuhan, Hubei province, China. Based on clinical findings, blood tests and chest radiographs, this disease was diagnosed as a virus-associated pneumonia. Sequence analysis revealed a novel coronavirus, called SARS-CoV-2 (formerly called 2019-nCoV), as the causative agent of pneumonia of unknown etiology. So far, the SARS-CoV-2 infection continues to spread, and this virus poses a serious public health threat. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…miRNAs express ubiquitously across species and play significant roles in the development and perform diverse regulatory functions in cells, including viral infections ( Głobińska et al, 2014 ; Rossi et al, 2015 ). In many cases, miRNAs have been proposed as minimally invasive markers for the early detection of diseases, and human encoded miRNAs could be the finest candidates for the development of miRNA-based therapeutics in the management of SARS-CoV-2 infection ( Bozgeyik, 2021 ). In this study, we purposed to investigate the levels of miR-200c-3p and miR-421-5p in admitted and recovered COVID-19 patients and seeking their correlations with inflammation and tolerance-related gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs express ubiquitously across species and play significant roles in the development and perform diverse regulatory functions in cells, including viral infections ( Głobińska et al, 2014 ; Rossi et al, 2015 ). In many cases, miRNAs have been proposed as minimally invasive markers for the early detection of diseases, and human encoded miRNAs could be the finest candidates for the development of miRNA-based therapeutics in the management of SARS-CoV-2 infection ( Bozgeyik, 2021 ). In this study, we purposed to investigate the levels of miR-200c-3p and miR-421-5p in admitted and recovered COVID-19 patients and seeking their correlations with inflammation and tolerance-related gene expressions.…”
Section: Discussionmentioning
confidence: 99%
“…Mir-200 family has been well characterized in cancer with numerous reports on its tumor suppressive action in multiple human cancers [ 271 , 272 ], including in lung cancer [ 81 , 273 ]. Members of this family can regulate ACE2, with miR-200c possibly the strongest candidate miRNA that can target ACE2 in respiratory cells [ 274 ]. Additionally, members of miR-200 family have been reported to regulate inflammation.…”
Section: Micrornas As Epigenetic Regulators Connecting Inflammation mentioning
confidence: 99%
“…It has been evident that upregulation of miR-181a is associated with upregulation of signaling cascades of adaptive immunity and inflammation [130] . Thus, forced expression of this miR can serve as a therapeutic agent for COVID-19 [131] . Another miRNA that can specifically be targeted for curing COVID-19 in patients with chronic kidney disease is miR-421 ( Fig.…”
Section: Kidney Disease and Covid-19mentioning
confidence: 99%
“…Another miRNA that can specifically be targeted for curing COVID-19 in patients with chronic kidney disease is miR-421 ( Fig. 2 ) [131] . Trojanowicz et al, have shown that miR-421 binds to 3'-UTR of the ACE2 mRNA [132] .…”
Section: Kidney Disease and Covid-19mentioning
confidence: 99%